Effect of crumb rubber and nano silica on the creep and drying shrinkage of roller compacted concrete pavement - Adamu, M. (GEOMATE International Society, 2018)
Roller compacted concrete (RCC) pavement is used mostly for heavy duty vehicle operations such as log sorting yards, intermodal yards for containers, parking areas for military vehicles and trucks and automobiles, and aircraft parking ramps. Therefore, it is subjected to long-term loading which can cause permanent deformation. Therefore in this study, the long-term creep and drying shrinkage of RCC pavement up to 1 year was studied. High volume fly ash (HVFA) RCC pavement was developed by replacing 50 cement with fly ash. A total of five RCC pavements were developed; one control mixture, two RCC pavement mixtures and two HVFA RCC pavement mixtures. The four mixtures were developed by replacing 10 fine aggregate with crumb rubber by volume and addition of 1 nano silica by weight of cementitious materials. The results showed that the creep and drying shrinkage of RCC pavement increases with time, and with the incorporation of crumb rubber and HVFA and decreases with the addition of nano-silica. The creep strain of RCC pavement mixtures can be predicted at any given time using their compressive strength and age of testing. Â© Int. J. of GEOMATE.